Subcontracting: A Study in the Framework of Administrative Contracts Under the Saudi System - Al-Mohana, Abdulrahman Abdulaziz Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2025)
This research aimed to study subcontracting in administrative contracts by clarifying the concept of subcontracting, analyzing the basic features of subcontracting in administrative contracts, and clarifying aspects of regulating the relationship within subcontracting within the scope of administrative contracts under the Saudi system. The research used the descriptive inductive approach, and data was collected from several secondary sources using a document analysis tool. The results of the study revealed that the concept of subcontracting is represented by a subsidiary agreement concluded by the original contractor with a third party, with the aim of fulfilling part of its contractual obligations with the administrative body. The study demonstrated that this type of contracting is distinguished by certain characteristics, such as the existence of a tripartite relationship and its being subordinate to the original contract. The study also indicated that the Saudi legislator did not leave this type of contracting unregulated, but rather established a clear legal framework for it in the Government Tenders and Procurement Law, permitting subcontracting on the condition of obtaining prior written approval from the administration, while specifying terms and controls aimed at protecting the public interest. The results also indicated that there are no multiple legal forms for subcontracting under the Saudi system. Rather, its concept is embodied in various fields of application, most notably the contracting and leasing sectors. Furthermore, the study results indicated that the relationship between the main contractor and the subcontractor is a contractual relationship subject to the general rules of civil law. Based on these findings, the study recommended the need to better implement subcontracting by administrative bodies enhancing transparency and oversight of projects, developing a unified procedural manual, developing qualification criteria, setting a maximum percentage of subcontracted work, and establishing an effective dispute resolution mechanism to ensure quality implementation and achieve the public interest.
Keywords: Subcontracting; Administrative Contracts; Original Contractor; Monitoring; Government Tenders and Procurement Law